2001
DOI: 10.1038/sj.ejcn.1601207
|View full text |Cite
|
Sign up to set email alerts
|

Does fat intake predict adiposity in healthy children and adolescents aged 2–15 y? A longitudinal analysis

Abstract: Objective: To investigate the relationship between food energy and macronutrient intake and body fatness assessed up to seven times between 2 and 15 y of age. Design: Prospective, observational study. Generalised linear estimating equations were used to evaluate the longitudinal relationship between body fatness and macronutrient intake. Regression analysis was used to assess whether body fatness at a particular age was predicted by intake at any of the previous ages. Setting: Community-based project in Adelai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 27 publications
4
67
0
9
Order By: Relevance
“…The second study found that young males who adhered to a DP rich in starch food sources at the age of fifteen had a 30% (p < 0.05) lower chance of being obese five years later 30 . There was no evidence of association between BMI and consumption of macronutrients (carbohydrate, protein and fat -% calories/ day) 15 , intake of dietary salt 16 , energy intake 29 and the habit of consuming milk, dairy products and calcium 10,22,23 .…”
Section: Body Mass Index (Bmi)mentioning
confidence: 88%
See 3 more Smart Citations
“…The second study found that young males who adhered to a DP rich in starch food sources at the age of fifteen had a 30% (p < 0.05) lower chance of being obese five years later 30 . There was no evidence of association between BMI and consumption of macronutrients (carbohydrate, protein and fat -% calories/ day) 15 , intake of dietary salt 16 , energy intake 29 and the habit of consuming milk, dairy products and calcium 10,22,23 .…”
Section: Body Mass Index (Bmi)mentioning
confidence: 88%
“…The age at baseline ranged from two 15 to 18 years old 16,17 . Follow-up had a minimal duration of two years 11,18,19 and maximum of 13 years 15,20 . The average duration of follow-up was 6.0 years (SD = 2.9) and median of five years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies found an association between high protein intake in infancy and later high fatness, 24,46 whereas others did not. 9,47 A study conducted in Danish children found an association with measures of body size (weight and height) but not with body fat. 48 We previously proposed that the characteristics of childhood obesity, that is, increased stature and body mass (lean and fat) 27 were the consequence of high protein intakes inducing changes in hormonal status.…”
Section: Factors Associated With An Early Ar and Increased Fatnessmentioning
confidence: 99%